Study on Steady-State Responses of High-Speed Vehicle Using Infinite Long Track Model - Wubin Cai; Maoru Chi (Shock and Vibration)
The coupled vehicle/track dynamic model is formulated through integrating a high-speed rail vehicle model with a slab track model via the wheel/rail contact model. The sliding window method is improved using the least square criterion to simulate the vehicle travelling along the infinite long track. The steady-state responses of a high-speed vehicle induced by the discrete sleepers and slab segments are investigated through numerical simulation and analysis of the experimental results. Also the validity of the coupled vehicle/track model is examined through comparing the simulation results with those acquired from field test measurements. The experimental and numerical results show that the wheel/rail contact forces fluctuate considerably as long as the sleeper passing frequency approaches the frequency of P2 resonance (wheelset and rail bouncing in phase on the slab). Increasing the damping of rail pads and primary suspension can lower the steady-state response amplitudes at the resonance region. The oscillations in the wheel/rail normal forces arising from the discrete slab segment excitation can be reduced by increasing the support stiffness of the CAM (cement asphalt mortar) layer under the slab.